Open Society
A documentary on George Soros with emphasis on the notion of “open societies.” The film looks into the philanthropic work of George Soros in Eastern Europe, particularly Bulgaria. It features interviews with: Dr. Marin Marinov, George Soros, Blaga Dimitrova (poetess), Yordan Radichkov (writer), Asparuh Georgiev (Chairman, Open Society Club – Pleven), Prof. Bogdan Bogdanov (Chairman, Open Society Fund - Sofia), Rousi Chanev (actor), Ognian Todorov (scholarship student of the Open Society Fund), Georgy Prohasky (Executive Director, Open Society Fund - Sofia), Peter Konstantinov (Writer), Vuzkressia Vihurova (Director, Department of Theater, New Bulgarian University), Miglena Nikolchina (Editor, “Literaturen Vestnik”), Svetla Ivanova (Editor-in-Chief, “Lettre Internationale”), Kamen Balkanski (Coordinator Visual Arts Program, Soros Center for the Arts), Kamen Fournadzhiev (Chairman, Open Society Club - Velingrad), Radka Koleva (Deputy Chairwoman, Open Society Club - Plovdiv), and Zhechka Kalinova (Chairwoman, Open Society Club – Rouse).